The Use of Fix Up Strategy to Improve The Students’ Reading Comprehension Skill of SMP Negeri 10 Parepare - Nursyuhada; Ammang Latifa (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2019)
Reading skill is one of skill in language teaching and learning, besides grammar and vocabulary. Reading is the important thing for students in the process of acquiring, learning, mastering and using the language they learn. Without having Reading ability or without read, student and teacher cannot understand, pay attention, listen, and of course read. Based on the observation in SMP Negeri 10 Parepare, the students cannot be read the English passage well because the students are lack of attention, analyze and understanding the reading passage Then, the researcher hopes this proplem will be solved through fix up Strategy. Therefore, the objective of this research is to find out and analyze the use of fix up Strategy able to improve the students Reading Comprehension of eight grade student of SMP Negeri 10 Parepare. This research used quasi experimental method by using two classes with pre-test and post-test design. The population of this research was the eight year students of SMP Negeri 10 Parepare. In sampling process was taken cluster random sampling and this sample of this research VIII.1 as experimental class with 31 students and VIII.4 as control class with 31 students. The students were give treatment with Narrative texts. The data were collected by using Reading comprehension test. The result of data analysis shows that the students’ reading comprehension improved significantly. It was showed by the mean score of pre-test and post-test was 52.45 and the post-test was 80.41 It showed that through fix up Strategy as a mcan improve the reading comprehension of tenth year students of SMP Negeri 10 Parepare. Furthermore, after analyzing the data by using the test formula, the result of t-test value in post-test was 2.948 and t-table value was (2.000) It means that the t-test value (2.948) was higher than t-table value (2.000) Those indicate that H1 was accepted and H0 was rejected and the students who were taught through fix up Strategy were better than the students who were taught through Think, pair and share. From the results above can be concluded that fix up Strategy as method can improve the Reading Comprehension of the Eight year students at SMP Negeri 10 Parepare.